Solving the Combined Heat and Power Dispatch Problem: A Semi-definite Programming Approach - Abimbola, Jubril; Adediji, A.O.; Olaniyan, O.A. (Electric power component and system, 2020)
Electronic power component and system,Vol. 40, Issue No.12, p.14